Delayed repair of multiple perforations compounded with formocresol osteo-gingival necrosis - Dipali Yogesh Shah; Sharmila Trimbak Khopade; Pinal Mahendra Jain; Ashwini Manish Dadpe (Wolters Kluwer Medknow Publications, 2018)
This case report describes the management of formocresol osteo-gingival necrosis in a mandibular molar with lingual and furcal perforations using resorbable demineralized bone matrix and mineral trioxide aggregate (MTA). Three-year postoperative follow-up showed a substantial resolution of the osseous defect as well as a clinically and radiographically sound periodontium. Despite an apparently poor prognosis, conservative management of the case using a combination of demineralized bone matrix and MTA led to a successful outcome. Further, this report warrants that formaldehyde-containing medicaments have no role in contemporary endodontics.